AI in Construction Project Management: Enhancing Efficiency and Reducing Costs - Siva Praneeth Reddy Gudibandi (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2025)
The integration of Artificial Intelligence in construction project management represents a transformative shift in how construction projects are planned, executed, and monitored. This article examines the current state of AI adoption in the construction industry, exploring its key applications, cost benefits, implementation challenges, and future opportunities. The article reveals that AI technologies are significantly improving project planning accuracy, enhancing real-time monitoring capabilities, optimizing resource allocation, and reducing both direct and indirect costs. Despite notable technical and organizational challenges, the construction industry is increasingly recognizing AI’s potential to address fundamental inefficiencies and drive innovation. The article demonstrates that AI implementation leads to substantial improvements in project predictability, safety compliance, operational efficiency, and stakeholder satisfaction, marking a crucial evolution in construction project management practices.